Adding God: Religious and Secular Press Framing in Response to the Insertion of "Under God" in the Pledge of Allegiance - Hatcher, Anthony (Journal of media and religion, 2008)
This study examines how the issue of adding "under God" to the Pledge of Allegiance in 1954 was framed and influenced by two forces-the Catholic Knights of Columbus and the secular Hearst newspapers. The time period under consideration is 1951-1954, from the initial use of "under God" in the Pledge within the Knights of Columbus to passage of the change into federal law. The Knights fraternity has been documented as the originator of the concept, and an examination of major Hearst newspapers reveals an attempt by the chain to usurp credit for the "under God" campaign.